KONSEP TABAYYUN DALAM KONTEKS MEDIA SOSIAL (PENAFSIRAN TABAYYUN DALAM AL-QUR’AN MENURUT QURAISH SHIHAB DALAM TAFSIR AL-MISBAH) - Yusuf Alami; Rajulul Azka (Yayasan An-Nur Meunara Baro, 2026)
Abstract: The development of social media has accelerated the flow of information, but at the same time increased the risk of spreading unverified news (hoaxes), which impacts the social, legal, and ethical aspects of communication. In the context of Islamic scholarship, the concept of tabayyun is a fundamental principle in approaching information to avoid error and harm. This study aims to explain the concept of tabayyun in the Qur’an, analyze Quraish Shihab’s interpretation in Tafsir Al-Mishbah, and examine the relevance and application of the concept of tabayyun in the context of social media. This study employs a qualitative method using a literature review approach (library research) through the analysis of Quranic verses related to tabayyun, Quraish Shihab’s interpretation, and literature on communication ethics and information verification in the digital age. The results of the study indicate that, according to Quraish Shihab, tabayyun emphasizes caution, thorough verification, and moral responsibility in receiving and disseminating information. This concept is relevant as a foundation for digital communication ethics to prevent the spread of hoaxes, protect individual dignity, and foster healthy and equitable communication on social media. This study is expected to strengthen digital literacy based on Qur’anic values and serve as an ethical guideline for society in addressing information challenges in the digital age.